Gemeentediakonaat as plaasvervanger vir staatsondersteunde sinodale barmhartigheidsdiens in die Ned. Geref. Kerk - André Oosthuizen; Piet Strauss (Acta Theologica)
The deaconate of the Dutch Reformed Church developed especially from 1934 to 1994 on the basis of the so-called "national theology" and "Boer Calvinism" and along the guidelines of the "National Reconstruction Programme" (NRP). Between these years the "national deaconate" developed into the most comprehensive and highly specialised synodal-managed and state-subsidized service of the church. Various people and synods reflected on the deformation phenomenon in the ecclesiastical deaconate and propagated a "deaconal reformation". The vocation of the church to be and to become a colonial deaconal congregation and community is fundamentally a vocation towards self-denial and aking up the cross.